Prevalence, predictors and selected outcomes of early sexual initiation among adolescents in secondary schools in Lugbe, Abuja, Nigeria: a mixed methods study - Uchechi Grace Okonta (BMJ Public Health)
Background Early sexual initiation is the onset of sexual intercourse below 15 years. Despite many negative effects of early sexual initiation, its prevalence has kept increasing globally over the past decades.Objective This study aims to determine the burden, identify risk factors and examine the selected outcomes of early sexual initiation among secondary school adolescents.Design The study was a school-based descriptive cross-sectional survey which employed quantitative and qualitative methods.Method A descriptive cross-sectional survey was conducted among 300 in-school adolescents aged 15–19 in Lugbe, Abuja. Data were collected using an interviewer-administered questionnaire. Focus group discussion was also conducted in six schools using a structured FGD Guide. The prevalence of early sexual initiation was determined. Descriptive and inferential statistical analysis was done including a binary logistic regression to determine the predictive factors and outcomes of early sexual initiation with statistical inference made at p value <0.05.Results The prevalence of early sexual initiation was 11%; 80% of the respondents who had initiated sex did so before age 15, while 20% had first sex at ages between 15 and 19. Gender, academic performance, communication with parents and peer pressure were significantly associated predictive factors. Pregnancy, abortion, sexually transmitted infections, loss of self-confidence, expulsion from school, poor academic performance and depression were associated outcomes. Four main themes were identified from the qualitative data: being in a romantic relationship, peer pressure, media and lack of parental communication and monitoring.Conclusion The study concluded that there is high prevalence of early sexual initiation among those who had initiated sex. Predictive factors such as peer pressure, parental communication and media influence can be addressed by the inclusion of sex education in school curriculum and training of peer educators, advocacy and health education for parents of adolescents.